Comparative Study of the Impact of Class Repetition and Mass Promotion on Students’ Academic Achievement in Anambra State - Eboatu, V. N. (European Scientific Journal, ESJ, 2017)
This study investigated the impact of the practice of class repetition and mass promotion of failed JSS1 students on their academic achievement in Anambra State. The causal comparative or ex-post-facto type of the survey research design was adopted with four research questions and four hypotheses guiding the study. The population of the study consisted of all failed Junior Secondary School (JSS1) students in Anambra State secondary schools in the base year (2004/2005), from which a sample of 636 was drawn. A researcher designed form was used to collect the students’ results. The statistical analysis of frequencies, range of scores, percentages and Pearson Product Moment Correlation were used to answer the research questions, while t-test was used to test the hypotheses. Findings of the study, among other things, show that the repeated students made a significant positive change in their repeated JSS1 and that the repeated students’ results were significantly better than those of the mass promoted group JSS2 results. Based on the findings, the researcher recommends that educational policy makers adopt an eclectic promotion policy that will enable the school managers repeat students in cases where it is felt that class repetition will enhance students’ learning and academic achievement.